Answer:
X = 3
You're welcome.
Step-by-step explanation:
- 3 + 3x = 2x – 13
Bring -3 to the right side of the equation by adding 3 to both sides
(- 3 + 3) + 3x = 2x – 13 + 3
0 + 3x = 2x - 10
3x = 2x - 10
Bring 2x to the other side by subtracting 2x to both sides
3x - 2x = 2x - 2x - 10
x = -10
Check:
-3 + 3(-10) = 2(-10) - 13
-3 + (-30) = -20 - 13
-33 = -33
Hope this helped!
~Just a girl in love with Shawn Mendes
Step-by-step explanation:
(x-2)^3 = x^3-6x^2+12x-8
-(x^3-6x^2+12x-8)=
-x^3+6x^2-12x+8
-x^3+6x^2-12x+8 -5=
y=-x^3+6x^2-12x+3
I attached the picture
Hourly Rate: $6.77
Federal Tax Income: $16.25
Other Federal Taxes: $12.43
Net Pay: $127.05
Answer:
c. 5 - 17
Step-by-step explanation:
a. -15 - 3 = -18
b. -3 - (-9) = 6
c. 5 - 17 = -12
d. -6 - (-6) = 0